Impact of fixed choice design on blockmodeling outcomes - Žnidaršič, Anja (Metodološki zvezki, 2012)
The main goal of blockmodeling is to reveal the essential structure of the network based on patterns of relationships. Social network data usually contain different types of errors and one of them is caused by some limitation of number of selected actors in the research design. The impact of fixed choice design compared to free choice design on the results of blockmodeling are studied through simulations. The resulting blockmodels are compared with two indices where position membership of actors and the structure of the blockmodels are examined. Limiting the number of actors that can be selected has an impact on delineated blockmodel structure where the deletion of ties has higher effect than addition of them.
Keywords: social network; socialna omrežja; blockmodeling; bločno modeliranje; fixed choice design; omejevanje izbir